2003
DOI: 10.1016/s0006-3495(03)70030-7
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Maintains Phase Separation in an Air-Dried Binary Lipid Mixture

Abstract: Mixing and thermal behavior of hydrated and air-dried mixtures of 1,2-dilauroyl-sn-glycero-3-phosphocholine (DLPC) and 1,2-distearoyl-d70-sn-glycero-3-phosphocholine (DSPCd-70) in the absence and presence of trehalose were investigated by Fourier transform infrared spectroscopy. Mixtures of DLPC:DSPCd-70 (1:1) that were air-dried at 25 degrees C show multiple phase transitions and mixed phases in the dry state. After annealing at high temperatures, however, only one transition is seen during cooling scans. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 48 publications
6
77
0
1
Order By: Relevance
“…It appears that Ca-alginate was not able to preserve the fatty acid site of phospholipid bilayers of freeze-dried bacterial cell envelopes during storage at room temperature, even at low a w s. Conversely, storage of CAMB at low a w s and in aluminum foil resulted in lower frequencies than that of the control. The presence of sugars (including mannitol) which interact with polar site of lipids during dehydration inhibits the interior apolar site of lipid changes, such as lipid phase transition and fusion (43), whereas storage at low a w s maintained the glassy state of sugars (31). Hence, lipid stability could be preserved.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that Ca-alginate was not able to preserve the fatty acid site of phospholipid bilayers of freeze-dried bacterial cell envelopes during storage at room temperature, even at low a w s. Conversely, storage of CAMB at low a w s and in aluminum foil resulted in lower frequencies than that of the control. The presence of sugars (including mannitol) which interact with polar site of lipids during dehydration inhibits the interior apolar site of lipid changes, such as lipid phase transition and fusion (43), whereas storage at low a w s maintained the glassy state of sugars (31). Hence, lipid stability could be preserved.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous work, it has been shown that trehalose slightly increase the phase transitions of model liposome membranes. 36 It has been proposed that sugars and polyols increase the stability of hydrated membranes due to their water-structuring properties, causing the lipid bilayer to became more closely packed due to an increase in interfacial tension. 36 Gelatin, which has also induced an increase in the membrane phase transition temperatures, may also exert its effects by the same mechanism.…”
Section: High Throughput Screening For Inhibitors Of Rsv Aggregationmentioning
confidence: 99%
“…36 It has been proposed that sugars and polyols increase the stability of hydrated membranes due to their water-structuring properties, causing the lipid bilayer to became more closely packed due to an increase in interfacial tension. 36 Gelatin, which has also induced an increase in the membrane phase transition temperatures, may also exert its effects by the same mechanism. Despite the fact that polyanions inhibited the rate of aggregation of RSV at 56˚C, they appeared to destabilize RSV protein structure.…”
Section: High Throughput Screening For Inhibitors Of Rsv Aggregationmentioning
confidence: 99%
“…The major bottleneck for direct incorporation of membrane proteins into GUVs is the dehydration step preceding the formation process. When (proteo)liposomes prepared from unsaturated lipids are dried, the transition temperature (T M ) increases by 70-80 (Ricker et al ., 2003). This causes the lipids to go from a liq uid crystalline to a gel phase, which induces lateral phase separation.…”
Section: Giant Unilamellar Vesiclesmentioning
confidence: 99%